2020
DOI: 10.1101/2020.06.23.166975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The development of attentional control mechanisms in multisensory environments

Abstract: AbstractAttentional control outside of the laboratory operates in multisensory settings, but the development of mechanisms subserving such control remains poorly understood. We investigated when, over the course of childhood, adult-like attentional control mechanisms begin to emerge. Children aged five, seven, and nine were compared with adults on behavioural performance in a computer game-like multisensory spatial cueing task, while simultaneous 129-channel EEG was recorded. M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 84 publications
(194 reference statements)
1
17
0
Order By: Relevance
“…To summarise, in the real world, attention should be captured more strongly by stimuli that are unpredictable (Schroeder et al 2015), but also by those unknown or without a clear meaning. On the other hand, stimuli with high strong spatial and/or temporal alignment across senses (and so stronger bottom-up salience) may be more resistant to such goal-based attentional control (suppression), as we have shown here (multisensory enhancement of attentional capture; see also Santangelo & Spence 2007;Matusz & Eimer 2011;van der Burg et al 2011;Turoman et al 2021;Fleming et al 2020). As multisensory distractors captured attention more strongly even in current, context-rich settings, this confirms the importance of multisensory salience as a source of potential bottom-up attentional control in naturalistic environments (see SOMs for a short discussion of this replication).…”
Section: How We Pay Attention In Naturalistic Settingsmentioning
confidence: 53%
See 4 more Smart Citations
“…To summarise, in the real world, attention should be captured more strongly by stimuli that are unpredictable (Schroeder et al 2015), but also by those unknown or without a clear meaning. On the other hand, stimuli with high strong spatial and/or temporal alignment across senses (and so stronger bottom-up salience) may be more resistant to such goal-based attentional control (suppression), as we have shown here (multisensory enhancement of attentional capture; see also Santangelo & Spence 2007;Matusz & Eimer 2011;van der Burg et al 2011;Turoman et al 2021;Fleming et al 2020). As multisensory distractors captured attention more strongly even in current, context-rich settings, this confirms the importance of multisensory salience as a source of potential bottom-up attentional control in naturalistic environments (see SOMs for a short discussion of this replication).…”
Section: How We Pay Attention In Naturalistic Settingsmentioning
confidence: 53%
“…Like in the former study, each experimental trial consisted of the following sequence of arrays: base array (In Experiments 1 and 3: randomly varied between 100, 250, and 450ms; in Experiments 2 and 4: 450ms), followed by distractor array (50ms), followed by a fixation point (150ms), and finally a target array (50ms, see Figure 1A). However, compared to the original Matusz and Eimer (2011) paradigm, the number of elements was reduced from 6 to 4 and targets were reshaped to look like diamonds rather than rectangles, as Experiment 1 served as an adult control for a different, developmental study (reported in Turoman et al, 2020a, 2020b). Thus, the base array contained four differently coloured sets of closely aligned dots, each dot subtending 0.1° × 0.1° of visual angle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations